Estudo e concepção de retificadores a três níveis com alto fator de potência utilizando técnicas de comutação não dissipativas - Tofoli, Fernando Lessa (2005)
This thesis proposes the study of single-phase and three-phase three-level rectifiers operating with unity power factor. By the investigation of several works in the literature, prominent characteristics such as minimized conduction losses, reduced number of components and low harmonic content of the input current can be addressed to the topologies. They are studied in order to determine the operating conditions and define the design procedure for power and control circuits. Furthermore, a passive lossless snubber is proposed to minimize switching losses, improving efficiency. Finally, analytical results are presented so that the performance of the converters can be evaluated, and important issues are discussed.